2010
DOI: 10.1136/bjsm.2009.062588
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder injuries in skeletally immature throwers: review and current thoughts

Abstract: The incidence of shoulder injuries in the paediatric athletic population continues to increase with increased participation particularly in throwing and overhead sports. While soft tissue injuries can occur, the physis remains the weak link and site of injury in many cases. Injury prevention targets proper throwing mechanics and the avoidance of overuse injuries by monitoring the amount of training and number of throws these young athletes are exposed to.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…It has been shown that contact pressure at the glenohumeral joint increases proportionally when horizontal abduction exceeds the coronal plane, with external rotation and 908 of shoulder abduction (Mihata, McGarry, Kinoshita, & Lee, 2010). However, the most dangerous manoeuvres during the volleyball attack are shoulder flexion during the elevation of the spiking arm, together with maximal external rotation (Leonard & Hutchinson, 2010;Page, 2011). Subacromial and internal impingement occurs predominantly against the anterior edge of the acromion and the coracoacromial ligament affecting the vasculature of these structures (Neer & Welsh, 1977;Page, 2011;Rathbun & Macnab, 1970).…”
Section: Discussionmentioning
confidence: 97%
“…It has been shown that contact pressure at the glenohumeral joint increases proportionally when horizontal abduction exceeds the coronal plane, with external rotation and 908 of shoulder abduction (Mihata, McGarry, Kinoshita, & Lee, 2010). However, the most dangerous manoeuvres during the volleyball attack are shoulder flexion during the elevation of the spiking arm, together with maximal external rotation (Leonard & Hutchinson, 2010;Page, 2011). Subacromial and internal impingement occurs predominantly against the anterior edge of the acromion and the coracoacromial ligament affecting the vasculature of these structures (Neer & Welsh, 1977;Page, 2011;Rathbun & Macnab, 1970).…”
Section: Discussionmentioning
confidence: 97%
“…Trial registration: Prospectively registered in February 6, 2017 under Clinical Trial Registry # NCT03044236 Background The shoulder complex is the most commonly injured body part in overhead and throwing athletes, accounting for 30% of all injuries (1,2). With the growing interest and participation in overhead sports, the incidence of shoulder pain and/ or injuries continues to increase (3)(4)(5). In fact, more than half of the general population will experience shoulder pain at one time or another in their lives (6).…”
Section: Discussionmentioning
confidence: 99%
“…Proximal humeral epiphysiolysis occurs due to repetitive rotational torque and distraction forces over the immature physis in overhead throwing athletes, especially baseball pitchers. [27][28][29] Other terms used to describe this phenomenon are "Little League Shoulder," epiphysitis, and a chronic Salter Harris I fracture of the proximal humerus. Epiphysiolysis most commonly occurs between ages 12 and 15 years when hormonal influence on the physis adversely affects its tensile resistive strength.…”
Section: Proximal Humeral Epiphysiolysis (Little League Shoulder)mentioning
confidence: 99%